2022
DOI: 10.1002/maco.202213530
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and passivation behavior of 6082‐T6 aluminum alloy in NaCl solution

Abstract: The corrosion and passivation behaviors of 6082-T6 aluminum alloy in 1.5 wt% NaCl solution with natural aeration were investigated by segmented electrochemical measurement combined with scanning electron microscope, transmission electron microscope, and X-ray diffractometer. The results showed that the active Mg dissolved from Mg 2 Si promoted the development of intergranular corrosion (IGC) and that local dissolutions of the matrix around the Si and AlFeMnSi particles are the initial sites for pitting corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Hasil penelitian menunjukkan bahwa ketahanan korosi paduan aluminium 2014 menurun seiring dengan meningkatnya suhu dan waktu perlakuan aging. Yang, dkk (2023) telah melakukan penelitian mengenai pengaruh suhu aging terhadap struktur mikro dan perilaku korosi paduan aluminium 6082. Hasil penelitian menginformasikan bahwa paduan tersebut memiliki kerapatan dan kedalaman korosi maksimum di bawah penuaan puncak, dan perlakuan penuaan berlebih mengoptimalkan perilaku korosi.…”
Section: Pendahuluanunclassified
“…Hasil penelitian menunjukkan bahwa ketahanan korosi paduan aluminium 2014 menurun seiring dengan meningkatnya suhu dan waktu perlakuan aging. Yang, dkk (2023) telah melakukan penelitian mengenai pengaruh suhu aging terhadap struktur mikro dan perilaku korosi paduan aluminium 6082. Hasil penelitian menginformasikan bahwa paduan tersebut memiliki kerapatan dan kedalaman korosi maksimum di bawah penuaan puncak, dan perlakuan penuaan berlebih mengoptimalkan perilaku korosi.…”
Section: Pendahuluanunclassified
“…Rymer et al [9] investigated the influence of artificial aging time on the precipitation characteristics and crack propagation behaviors of 6060 aluminum alloy. Li et al [10] showed that artificial aging temperatures significantly influenced the precipitation characteristics and corrosion behaviors of the extruded 6082 aluminum alloy. Liu et al [11] reported that when the new type of 6005A aluminum alloys were subjected to the underage state, their resistance against fatigue crack growths showed the optimum.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 19 observed significant deterioration in the mechanical properties of 7A85 aluminum alloy due to exposure-induced pitting corrosion and intergranular corrosion in atmospheric conditions. Li et al 20 noted that pitting in the corrosion of 6082-T6 aluminum alloy typically initiates around the matrix near reinforcement particles. Kucharikova et al 21 investigated the impact of the iron-rich phase, silicon particles, and corresponding alloy matrix on the corrosion properties of aluminum alloys.…”
mentioning
confidence: 99%